Substance Use and the Self-Management of Persistent Symptoms of COVID-19. (12th May 2023) - Veliz, Philip T.; Zhou, Weijiao; Smith, Sheree; Larson, Janet L.
Abstract: Background : Understanding the self-management practices of persistent symptoms of SARS-Cov-2 (COVID-19) is critical given the misinformation that has been presented about this disease in the U.S. The purpose of this descriptive study is to assess the self-management of persistent symptoms of COVID-19 with commonly used and misused substances (i.e., alcohol, marijuana and commonly prescribed medications) among adults in the U.S. Methods : The data for this study comes from a cross-sectional survey of U.S. adults that was designed to broadly assess symptom burden, persistent symptom patterns, self-efficacy for symptom management and self-management strategies among people who experienced persistent/Long COVID. Multiple logistic regression analyses were used to assess how symptom length of COVID-19 was associated with the use of several substances to manage these persistent symptoms. Results : The analysis found that adults who had COVID-19 symptoms that persisted for 13 weeks or longer had higher rates of using alcohol (27.3%), marijuana (30.9%) and prescription tranquilizers (21.4%) to manage these symptoms when compared to their adult peers who had COVID-19 symptoms persist for only 4 weeks or less. For instance, the odds of indicating the use of marijuana (AOR = 4.21 95% CI = 1.68, 10.5) to manage COVID-19 related symptoms was roughly four times higher for respondents who had COVID-19 symptoms persist for 13 weeks or longer when compared to respondents whose COVID-19 symptoms persisted for only 4 weeks or less. Conclusion : The findings suggest that screening of substance use disorders should be considered among healthcare providers who are treating adults who have persistent symptoms of COVID-19.